Investigation of the Depth Stability of the Furrow Former of a Saxaul Seed Planter (Texas Journal of Agriculture and Biological Sciences, 2025)
The article presents analytical expressions for determining the depth stability of the furrow former of a saxaul seed planter and identifies the factors that influence its performance